2012
DOI: 10.1111/j.1526-4637.2012.01340.x
|View full text |Cite
|
Sign up to set email alerts
|

Placebo Response Changes Depending on the Neuropathic Pain Syndrome: Results of a Systematic Review and Meta-Analysis

Abstract: Placebo response is influenced by the pain syndrome evaluated. These differences should be considered when evaluating novel compounds for the treatment of neuropathic pain conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 158 publications
(159 reference statements)
4
33
0
Order By: Relevance
“…44 Pain due to HIV-related painful polyneuropathy and radiculopathy seems more refractory than other pain conditions in our meta-analysis. This may be due to large placebo responses in HIV-related neuropathy trials, 45 a distinct clinical phenotype in subgroups of patients with radiculopathy, 46 or psychological/psychosocial comorbidites, often neglected in large trials. Topical agents have no known relevance for use in central neuropathic pain, and this is clearly stated in our recommendations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…44 Pain due to HIV-related painful polyneuropathy and radiculopathy seems more refractory than other pain conditions in our meta-analysis. This may be due to large placebo responses in HIV-related neuropathy trials, 45 a distinct clinical phenotype in subgroups of patients with radiculopathy, 46 or psychological/psychosocial comorbidites, often neglected in large trials. Topical agents have no known relevance for use in central neuropathic pain, and this is clearly stated in our recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…One major issue is the placebo response which seems to have increased in recent trials of neuropathic pain and may lead to an underestimation of drug effects. 51 Placebo response has been found to be higher in HIV-related neuropathies, 45 and in patients with low or variable pain scores at inclusion. 52 Conversely it seems to be lower in postherpetic neuralgia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…62 In contrast, placebo response seems to be lower in postherpetic neuralgia. 26 Several analyses from recent trials in NP have reported that the placebo response was also higher in patients with low or variable pain scores at inclusion. 34,39 Other studies are needed to further explore the potential reasons for such a high placebo response in NP.…”
Section: High Placebo Responsementioning
confidence: 98%
“…A variety of factors including patient expectation, emotions such as anxiety and mood all have significant effects on the complex neurobiological process that lies behind placebo analgesia 79 80. Different types of neuropathic pain are affected in different ways by the placebo effect 81. While different treatments may have hugely differing strengths of placebo effect depending on multiple complex patient and treatment factors, it has been argued that the placebo effect of sham surgery is likely to be particularly strong 82.…”
Section: Considering Drivers Of Pain In the Diagnosis And Management mentioning
confidence: 99%